2009
DOI: 10.1093/jb/mvp066
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Membrane-Bound Serine Protease Matriptase on the Cell Surface

Abstract: Matriptase is a type II transmembrane serine protease. The activation (i.e. conversion of the single-chain pro-form to the disulphide-linked-two-chain active form) of this enzyme is known to occur via a mechanism requiring its catalytic triad. We reported previously that the activated enzyme was produced in the conditioned medium when full-length rat matriptase was expressed in monkey kidney COS-1 cells. The present study aimed to address when and where the matriptase activation occurs. COS-1 cells expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…Figure 2b shows that the medium sample from cells transfected with pcDNA-WT-matriptase and pSec-HAI66K produced a band at the 28-kDa position (right lane, indicated by closed arrowhead), whereas those from cells transfected with parental vectors and pcDNA-WT-matriptase alone did not (left and middle lanes, respectively). These results confirm our previous findings (Tsuzuki et al 2005;Miyake et al 2009) that co-expression of HAI-1 is important for the detection of WT-matriptase from conditioned media.…”
Section: Detection Of Wt-matriptasesupporting
confidence: 92%
See 4 more Smart Citations
“…Figure 2b shows that the medium sample from cells transfected with pcDNA-WT-matriptase and pSec-HAI66K produced a band at the 28-kDa position (right lane, indicated by closed arrowhead), whereas those from cells transfected with parental vectors and pcDNA-WT-matriptase alone did not (left and middle lanes, respectively). These results confirm our previous findings (Tsuzuki et al 2005;Miyake et al 2009) that co-expression of HAI-1 is important for the detection of WT-matriptase from conditioned media.…”
Section: Detection Of Wt-matriptasesupporting
confidence: 92%
“…For convenient detection, S-tag was fused to the N-terminus of the protein (Tsuzuki et al 2005). This variant was shed from cellsurface membrane and was detected mainly as a 58-kDa band from medium samples (Miyake et al 2009). We have recently shown that HAI66K inhibits secreted variants of r-matriptase in vitro (Kojima et al 2009b).…”
Section: Designation Of R-hai-1 Variantsmentioning
confidence: 95%
See 3 more Smart Citations